ANALISIS PERBANDINGAN KINERJA KEUANGAN PERUSAHAAN INDUSTRI BARANG DAN KONSUMSI SUB SEKTOR ROKOK YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) (Studi Kasus pada PT. Bentoel Internasional Investama Tbk dan PT. Wismilak Inti Makmur Tbk Periode 2016-2020) - Siti Jainab Lukfiatih Bugis; Dwiyani Sudaryanti; Hariri Hariri (e_Jurnal Ilmiah Riset Akuntansi, 2021)
The success of a company in running its business can be seen from the company's financial performance which can be seen from the reports that describe the company's finances from a certain period. The good and bad condition of the company can be seen from the analysis of the company's financial statements. In this case, ratio analysis can be used to provide an overview of the financial performance of the financial performance regarding the sustainable development of the company the company does business. This study aims to find out how the performance comparison of financial ratios at the company PT. Bentoel Internasional Investama Tbk and PT. Wismilak Inti Makmur Tbk. The data analysis method used in this study is a quantitative descriptive analysis method using financial ratios. The results of this study indicate that in terms of the Liquidity Ratio Proxy Current Ratio and the Solvency Ratio Proxy Debt to Asset Ratio there is a significant difference and in terms of the ratio of the Total Assets Turnover Proxy Activity and the Profitability Ratio of the Return on Equity Proxy there is no significant difference.Keywords: financial performance; Liquidity Ratio Proxy Current Ratio; Solvency Ratio Proxy Debt to Asset Ratio; Proxy Activity Total Assets Turnover; Profitability Ratio Proxy Return on Equity.